Pathways for resilience in Mediterranean cork oak land use systems - Acácio, Vanda; Holmgren, Milena (Annals of Forest Science, 2012)
& Context Loss of woodlands and degradation of vegetation and soil have been described for all Mediterranean-type ecosystems worldwide. In the Western Iberian Peninsula, overexploitation of evergreen cork oak land use systems has led to soil erosion, failures in oak recruitment, and loss of forests. Degraded and dry sites are quickly colonised by pioneer heathland rockrose (Cistus spp.) shrubs forming highly persistent patches. & Aims Although traditionally shrublands have been considered as a transient successional state, we present evidence that they can represent persistent alternative states to former cork oak forests. & Review trends and conclusions We first describe how Mediterranean vegetation evolved in the Iberian Peninsula and the role of fire and long-term human management as main disturbances. We then discuss alternative pathways through state-and-transition models indicating the ecological and land use variables that halt cork oak regeneration and recruitment and drive vegetation transitions towards persistent shrublands. Unless concerted management actions and restoration programmes are undertaken, the cork oak land use systems will not be sustainable.
Keywords: alternative stable state; cistus; mediterranean-type ecosystem; Quercus suber; resilience; Restoration

Oak persistence in Mediterranean landscapes: the combined role of management, topography, and wildfires - Acácio, Vanda; Holmgren, Milena (Ecology and society, 2010)
Mediterranean ecosystems have been shaped by a history of human and ecological disturbances. Understanding the dynamics of these social-ecological systems requires an understanding of how human and ecological factors interact. In this study, we assess the combined role of management practices and biophysical variables, i.e., wildfire and topography, to explain patterns of tree persistence in a cork oak (Quercus suber L.) landscape of southern Portugal. We used face-to-face interviews with landowners to identify the management practices and the incentives that motivated them. We used aerial photographs and a Geographic Information System (GIS) to classify vegetation patch-type transitions over a period of 45 years (1958-2002) and logistic regression to explain such changes based on management and biophysical factors. The best model explaining vegetation transitions leading to cork oak persistence in the landscape included both biophysical and management variables. Tree persistence was more likely to occur on steeper slopes, in the absence of wildfires, and in the absence of understory management. We identified ecological, ideological, and economical barriers that preclude oak persistence and that are important to consider in implementing efficient environmental policies for adequate conservation and reforestation programs of Mediterranean cork oak landscapes.
Keywords: agroforestry system; alternative ecosystem state; Cistus ladanifer; Land degradation; Mediterranean; Portugal; Quercus suber; Shrub encroachment; succession; vegetation transition

Multiple Recruitment Limitation Causes Arrested Succession in Mediterranean Cork Oak Systems - Acácio, Vanda; Holmgren, Milena; Jansen, Patrick a.; Schrotter, Ondrej (Ecosystems, 2007)
Lack of tree regeneration and persistency of species-poor shrublands represent a growing problem across Mediterranean evergreen oak forests. What constrains forest regeneration is poorly understood, and restoration attempts have been largely unsuccessful. We assessed the contribution of four different mechanisms of tree recruitment limitation (that is, source, dispersal, germination, and establishment) in a cork oak (Quercus suber) system in southern Portugal. Using a combination of ﬁeld studies and experiments, we quantiﬁed seed production, seed removal and dispersal, seed survival and germination, seedling establishment and survival, as well as cork oak natural regeneration for the three dominant vegetation types in this system (Cistus ladanifer shrubland, oak forest, and oak savanna). We found that all four forms of cork oak recruitment limitation were signiﬁcantly more severe in shrublands than in oak forests and savannas, so that oak seedling recruitment in shrubland was impeded in multiple ways. Our results explain why transitions from shrublands to oak savannas and forests are extremely difﬁcult, and that the release from arrested succession in this system requires the simultaneous relief of multiple constraints on recruitment limitation in the early life history of oaks. These results have important implications for the restoration
Keywords: alternative states; Cistus ladanifer; Facilitation; forest regeneration; Quercus suber; seed dispersal; seed predation; seedling establishment; Shrub encroachment

Multiple Recruitment Limitation Causes Arrested Succession in Mediterranean Cork Oak Systems - Acácio, Vanda; Holmgren, Milena; Jansen, Patrick a; Schrotter, Ondrej (Ecosystems, 2007)
Lack of tree regeneration and persistency of species-poor shrublands represent a growing problem across Mediterranean evergreen oak forests. What constrains forest regeneration is poorly understood, and restoration attempts have been largely unsuccessful. We assessed the contribution of four different mechanisms of tree recruitment limitation (that is, source, dispersal, germination, and establishment) in a cork oak (Quercus suber) system in southern Portugal. Using a combination of ﬁeld studies and experiments, we quantiﬁed seed production, seed removal and dispersal, seed survival and germination, seedling establishment and survival, as well as cork oak natural regeneration for the three dominant vegetation types in this system (Cistus ladanifer shrubland, oak forest, and oak savanna). We found that all four forms of cork oak recruitment limitation were signiﬁcantly more severe in shrublands than in oak forests and savannas, so that oak seedling recruitment in shrubland was impeded in multiple ways. Our results explain why transitions from shrublands to oak savannas and forests are extremely difﬁcult, and that the release from arrested succession in this system requires the simultaneous relief of multiple constraints on recruitment limitation in the early life history of oaks. These results have important implications for the restoration
Keywords: alternative states; Cistus ladanifer; Facilitation; forest regeneration; Quercus suber; seed dispersal; seed predation; seedling establishment; Shrub encroachment